The effect of the proportion of Modern European ancestry on grower and sow performance of pigs in smallholder systems in Uganda - Babigumira, Brian Martin; Sölkner, Johann; Mészáros, Gábor; Wurzinger, Maria; Pfeiffer, Christina; Lewis, Craig R. G.; Lukuyu, Ben; Ouma, Emily; Marshall, Karen (Frontiers in Genetics, 2023)
Several factors, including breed, lead to divergent performance of pigs for production and reproduction traits in different environments. A recent genomics study showed that Modern European (ME) pig breeds contribute to the ancestry of smallholder pigs in Hoima and Kamuli districts, Uganda. These pigs were also involved in a longitudinal study with several traits recorded, including 540 body weights (WT) of 374 growing pigs, 195 records of total number of piglets born alive (TBA) of 157 sows and 110 total number weaned (TNW) records of 94 sows. Linear mixed effects models were used to test for the significance of environmental effects, including housing system, geographic location, season when the events occurred as well as animal specific effects like age, sex, parity, and farrow-to-weaning interval. Stepwise model reduction starting from models with all main effects and pairwise interactions was applied. The final models were then expanded to include proportions of Modern European (ME) ancestry for the subset of animals genotyped, following genomic ancestry analysis based on a Porcine 50K SNP Chip. ME ancestry proportions ranged from 0.02 to 0.50 and were categorized into three classes (low/medium/high ME) based on 33% quantiles. The effects of ME classes on WT and TBA were not significant. ME showed a significant effect on TNW. Sows with high proportion of ME weaned 2.4 piglets more than the low group, the medium ME group being intermediate. This study used genomic data to investigate the effects of genetic ancestry on the performance of smallholder pigs in Uganda. The proportion of Modern European ancestry did not exceed 0.50, therefore not allowing comparison of local versus pure 'exotic' types of pigs. For the range of ancestries observed, which is the relevant one for current smallholder systems in Uganda, differences were small for body weight of growing pigs and number of piglets born alive, while higher proportions of ME ancestry resulted in significantly more piglets weaned. Availability of genotypes of a higher number of growing pigs would have been beneficial for drawing conclusions on the effect of ME ancestry on the growth rates of smallholder pigs in Uganda.